ANALISIS PENGARUH CYBER PUBLIC RELATIONS TERHADAP KESADARAN MEREK SEBUAH PERGURUAN TINGGI SWASTA MENGGUNAKAN STUCTURE EQUATION MODELLING (SEM) - Hidayatullah, Mila; Syukron Anshori, Muhammad; Hudaya , Chairul (Jurnal TAMBORA, 2021)
This research is focused on the influence of public relations activities (PublicRelations-PR) through the use of the internet (Cyber ??PR) to brand awarenessa private college. The purpose of this research is to find outhow the influence of cyber PR activities carried out by the University Public RelationsSumbawa Technology (UTS) through social media such as Facebook, Youtube andInstagram towards increasing UTS brand awareness. ResearchThis method uses quantitative methods with SPSS structural equation modeling (SEM)to compile a model of research results. The sample population used inThis research is the community of Sumbawa sub-district with the age criteria 15-29year in which 124 respondents filled out a questionnaire as a representation of 16,770 peoplethe people of Sumbawa for that age category. From the results of the F test there is an influencesimultaneous between independent variables (Facebook, Instagram and Youtube variables)to the dependent variable (Brand Awareness). Meanwhile, the results of the t test are obtainedthat the Instagram variable has a significant influence onincrease in UTS campus brand awareness.